Peningkatan Pengetahuan Masyarakat Desa Kaloling Kec. Gatarangkeke Kab. Bantaeng Terhadap Bahaya Residu Pestisida Bagi Kesehatan - Rahmawati Rahmawati; Hasnah Hasnah (Lontara Abdimas : Jurnal Pengabdian Kepada Masyarakat, 2020)
Abstract The attack of plant pests (OPT) that almost occur in every planting season encourages farmers to use synthetic pesticides in crop pest control measures. Pesticide residues in the environment are a bad result of using or direct application by spraying. The Kaloling Village farming community has never received counseling about occupational safety and health, especially to farmers related to the use of pesticides. The output target of the implementation of this community service activity is to increase community knowledge in Kaloling Village, Gantarang Keke Subdistrict, Bantaeng Regency, about the dangers of pesticide residues for health. The method of implementation includes surveys and permits as well as the preparation of facilities and infrastructure, exposure to counseling material about the dangers of synthetic pesticide residues, while also conducting a discussion phase between the community members and providing feedback as an evaluation. Based on the results of counseling shows that the lack of knowledge and understanding, as well as the awareness of farmers in the use of pesticides by not following instructions on the pack, not using personal protective equipment (PPE) and not paying attention to the direction of the wind are risk factors to accelerate pesticide exposure in farmers' bodies. The effects of pesticide poisoning can cause symptoms of vomiting, diarrhea, dyspnea, blurred vision, paresthesia, chest pain. The final activity of the extension was carried out an evaluation to the farmers as extension participants about the level of understanding of the extension material, with the hope that this activity could increase farmers' knowledge.